Support Region of Semilogarithmic Quantizer for Laplacian Source - Zoran H. Peric; Sinisa B. Suzic; Tijana V. Delic; Nikola Simic (Elektronika ir Elektrotechnika, 2018)
The overall distortion of semilogarithmic A law quantizer is influenced by its support region, as well as parameter A. Current solutions require numerical determination of optimal support region and larger processing time, i.e. simple closed-form solutions for finding optimal values of these two parameters are not provided. In this paper, iterative and closed-form solutions for determination of the support region of semilogarithmic A law quantizer for Laplacian source, unite variance and a set of bit-rates 6 bits/sample−10 bits/sample are proposed. The performance of proposed solutions is compared to the optimal numerical results.